Characterization of Recombinant Fluoroquinolone-Resistant Pneumococcus-Like Isolates - Balsalobre, Luz (American Society for Microbiology, 2013)
Fourteen fluoroquinolone-resistant streptococcal isolates with recombinant DNA topoisomerase genes, preliminarily identified as pneumococci, were further characterized using phenotypic and genotypic approaches. Phenotypic tests classified them as atypical pneumococci. Phylogenetic relationships were analyzed by using the sequences of seven housekeeping alleles from these isolates and from isolates of Streptococcus pneumoniae, Streptococcus mitis, Streptococcus oralis, and Streptococcus pseudopneumoniae. Four isolates grouped with S. pneumoniae, seven grouped with S. pseudopneumoniae, and three grouped with S. mitis. These results generally agreed with those obtained with an optochin susceptibility test and with the organization of the atp operon chromosomal region, encoding the F(o)F(1) H(+)-ATPase (the target of optochin). All seven isolates grouping with S. pseudopneumoniae share the same spr1368-atpC-atpA gene order; all four grouping with S. pneumoniae share the spr1368-IS1239-atpC-atpA order, and two out of the three grouping with S. mitis share the spr1284-atpC-atpA order. In addition, evidence for recombination within the seven housekeeping alleles of the S. pseudopneumoniae population was provided by several methods: the index of association (0.4598, P < 0.001), the pairwise homoplasy index, and the split-decomposition method. This study confirms the existence of pneumococci among the alpha-hemolytic streptococci with DNA topoisomerase genes showing a mosaic structure and reveals a close relationship between atypical pneumococci and S. pseudopneumoniae.